Investor sentiment and stock market: Evidence from China - Zhou, Xiaoqing (2022)
This study carefully examines the relationship between investor sentiment and stock market returns, investor sentiment and stock market volatility in the Chinese stock market during the sample period from January 2003 to May 2022. First, the average closed-end fund discount, share turnover, the number on IPOs, average first-day returns on IPOs, the number of new investor accounts, and the consumer confidence index are used as proxy variables and a comprehensive index of investor sentiment suitable for the Chinese stock market is also constructed using Principal component analysis. Then, the positive relationship between investor sentiment and stock market returns was determined by using Vector autoregressive, and the bidirectional causality relationship between the two was further clarified by using the Granger causality test. Afterwards, GARCH is applied to capture market volatility and the relationship between investor sentiment and stock market volatility was tested empirically. The results show that there is also a positive relationship between investor sentiment and stock market volatility, and this effect is intertemporal. Finally, based on the findings of the paper, this research puts forward relevant suggestions for investors and regulators respectively.